2023
DOI: 10.2147/jhl.s383916
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Excellence in Knee Arthroplasty: Developing Optimal Patient Care Pathways and Inspiring Knowledge Transfer of Advanced Surgical Techniques

Filippo Migliorini,
Martina Feierabend,
Ulf Krister Hofmann

Abstract: Osteoarthritis of the knee is common. Early sports trauma or cartilage defects are risk factors for osteoarthritis. If conservative treatment fails, partial or total joint replacement is often performed. A joint replacement aims to restore physiological biomechanics and the quality of life of affected patients. Total knee arthroplasty is one of the most performed surgeries in musculoskeletal medicine. Several developments have taken place over the last decades that have truly altered the way we look at knee ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 138 publications
0
2
0
Order By: Relevance
“…One notable benefit is the enhanced precision provided by robotic systems. Recent studies, such as the one conducted by Migliorini et al (2023), demonstrated a significant improvement in implant placement accuracy during knee arthroplasty when utilizing robotic assistance. This heightened precision can contribute to optimal alignment, improving joint function and longevity (Migliorini et al, 2023).…”
Section: Robotics and Robot-assisted Techniques In Orthopaedic Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…One notable benefit is the enhanced precision provided by robotic systems. Recent studies, such as the one conducted by Migliorini et al (2023), demonstrated a significant improvement in implant placement accuracy during knee arthroplasty when utilizing robotic assistance. This heightened precision can contribute to optimal alignment, improving joint function and longevity (Migliorini et al, 2023).…”
Section: Robotics and Robot-assisted Techniques In Orthopaedic Surgerymentioning
confidence: 99%
“…Recent studies, such as the one conducted by Migliorini et al (2023), demonstrated a significant improvement in implant placement accuracy during knee arthroplasty when utilizing robotic assistance. This heightened precision can contribute to optimal alignment, improving joint function and longevity (Migliorini et al, 2023). Moreover, robotic-assisted surgery facilitates minimally invasive procedures, as evidenced by outcomes in hip resurfacing reported by Remily et al (2021).…”
Section: Robotics and Robot-assisted Techniques In Orthopaedic Surgerymentioning
confidence: 99%